Crystal orientation fabric anisotropy causes directional hardening of the Northeast Greenland Ice Stream - Gerber, Tamara Annina; Lilien, David A; Rathmann, Nicholas Mossor; Franke, Steven; Young, Tun Jan; Valero-Delgado, Fernando; Ershadi, M Reza; Drews, Reinhard; Zeising, Ole; Humbert, Angelika; Stoll, Nicolas; Weikusat, Ilka; et al. (Nature Communications, 2023)
Funding: This research was undertaken, in part, thanks to funding from the Canada Excellence Research Chairs Programme and has been financially supported by the Villum Investigator Project IceFlow (Grant No. 16572 to D.D.-J.). Radar development was further supported by funding from the University of Alabama. EGRIP is directed and organised by the Centre for Ice and Climate at the Niels Bohr Institute, University of Copenhagen. S.F. received funding from the German Academic Exchange Service (DAAD): Forschungsstipendien für promovierte Nachwuchswissenschaftlerinnen und -wissenschaftler. M.R.E. was supported by a DFG Emmy Noether grant (grant no. DR 822/3-1). The dynamic mass loss of ice sheets constitutes one of the biggest uncertainties in projections of ice-sheet evolution. One central, understudied aspect of ice flow is how the bulk orientation of the crystal orientation fabric translates to the mechanical anisotropy of ice. Here we show the spatial distribution of the depth-averaged horizontal anisotropy and corresponding directional flow-enhancement factors covering a large area of the Northeast Greenland Ice Stream onset. Our results are based on airborne and ground-based radar surveys, ice-core observations, and numerical ice-flow modelling. They show a strong spatial variability of the horizontal anisotropy and a rapid crystal reorganisation on the order of hundreds of years coinciding with the ice-stream geometry. Compared to isotropic ice, parts of the ice stream are found to be more than one order of magnitude harder for along-flow extension/compression while the shear margins are potentially softened by a factor of two for horizontal-shear deformation. Peer reviewed